Can a linking crosswalk table be applied to a different population? An independent validation study for a crosswalk between BSI depression and PROMIS depression scales - Xiaodan Tang; Benjamin D. Schalet; Patrick Janulis; Michele D. Kipke; Aaron Kaat; Brian Mustanski; Michael E. Newcomb; Amy Ragsdale; Soyeon Kim; Sue Siminski; Pamina M. Gorbach (PLoS ONE, 2022)
A linking procedure establishes a “bridge” between the scores from different patient-reported outcome (PRO) instruments that measure similar constructs. After developing a linking relationship however, it is critical to evaluate whether this relationship can be generalized to different groups. Our study aims to validate a published crosswalk for score conversion between the Brief Symptom Inventory Depression subscale and the Patient-Reported Outcomes Measurement Information System Depression 8a using an independent sample. Data were from a sample of young men who have sex with men (MSM), which differs in terms of participant age, race, and ethnicity from the sample used to develop the existing crosswalk. The validity of the newly derived crosswalk was evaluated in terms of the correlation, mean difference and standard deviation between the observed and the linked scores. The two crosswalks were further compared to evaluate if the difference was within an acceptable range. More than half of the item parameters obtained from the two samples were found to overlap in their confidence intervals. Differences between each pair of scores in the two crosswalks was within three T-score points, well within the range of each crosswalk score’s standard error. This study concludes that an existing crosswalk is replicable on a sample that differs from that used for crosswalk development, but future research should continue to examine the generalizability of the linked parameters and evaluate the reproducibility of this crosswalk to other populations.